Antiviral effect of amiloride on replication of foot and mouth disease virus in cell culture. (October 2019) - Gong, Mei-jiao; Chang, Yan-yan; Shao, Jun–jun; Li, Shi-fang; Zhang, Yong-guang; Chang, Hui-yun
Abstract: Recently, amiloride was shown to potently suppress Coxsackievirus B3 (CVB3) replication. In the current study, we investigated whether amiloride could also exhibit antiviral activity against foot-and-mouth disease virus (FMDV), which belongs to the same family ( Picornaviridae ) as CVB3. We found that amiloride exerted antiviral activity in a dose-dependent manner against two strains of FMDV in IBRS-2 cells, with slight cytotoxicity at 1000 μM. Besides, amiloride did not inhibit the attachment and entry of FMDV in IBRS-2 cells, but prevented early viral replication. These data implied that amiloride could be a promising candidate for further research as a potential antiviral drug against FMDV infection. Highlights: This was the first study to demonstrate the antiviral activity of amiloride against FMDV. Amiloride did not suppress the attachment and entry of FMDV into the cell. The antiviral effect of amiloride occurred in the early phases of FMDV replication.